MODERN APPROACH TO PEDIATRIC PALLIATIVE CARE ORGANIZATION - Yu.A. Shcherbuk; A.S. Simakhodskiy; L.V. Erman; Yu.A. Punanov ("Paediatrician" Publishers LLC, 2011)
Organization of palliative care provided to children with oncology and other life-threatening (fatal) conditions and diseases must be a compulsory part of a state pediatric healthcare service. In this article various organizational issues of the above mentioned service are being discussed. Key words: children, pediatric oncology, palliative care, organization. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (3): 16-20)